Potentiodynamic polarization behavior and microscopic examination of tungsten carbide hard metal materials in supported ammoniacal medium - Randhawa N.S.; Katiyar P.K. (My University, 2025)
Electrochemical methods for the recycling of tungsten carbide (WC-10Co) resources suffer from passivation in the acidic medium caused by WO3 and also in NaOH electrolytes, due to hydroxide formation. We found that an ammoniacal solution is a promising electrolyte for sustainable electrochemical dissolution of both tungsten (W) and cobalt (Co). The ammoniacal medium performs greatly when supported with Cl-, SO42- and CO32- ions. Poor dissolution/corrosion tendency of WC-10Co in a diluted NH4OH solution enhanced many folds in the presence of Cl-, SO42- and CO32- ions. Among these supporting ions, Cl- emerged as the most suitable for the electrochemical leaching of W and Co from the WC-10Co, accompanying the least noble behavior of WC-10Co. An electrolyte composed of 150 g/L of ammonia and 5% (w/v) of NH4Cl yielded the maximum anodic current density. Microscopic examination of the electrochemically treated samples shows scattered active sites responsible for the oxidative dissolution of WC-10Co. The usefulness of W and Co dissolution in ammonia-additive salt followed the order NH4OH-NH4Cl>NH4OH-(NH4)2SO4>NH4OH-(NH4)2CO3. © 2020, Sociedade Portuguesa de Electroquimica. All rights reserved.